Successful Treatment of Mediastinal Unicentric Castleman's Disease Using Video-Assisted Thoracoscopic Surgery with Preoperative Embolization. (30th September 2013) - Amano, Yosuke; Takai, Daiya; Ohishi, Nobuya; Shinozaki-Ushiku, Aya; Fukayama, Masashi; Akahane, Masaaki; Nakajima, Jun; Nagase, Takahide
Abstract : Unicentric Castleman's disease is a rare, benign lymphoproliferative disorder that is curable with surgical resection. However, significant bleeding often occurs during surgery because of tumor hypervascularity. We herein present a case of hyaline-vascular-type mediastinal unicentric Castleman's disease, successfully resected using video-assisted thoracoscopic surgery with preoperative embolization. In the present case, tumor hypervascularity and feeding vessels were revealed by computed tomography (CT), which led us to perform preoperative angiography and embolization to the tumor feeding arteries to reduce intraoperative bleeding. Castleman's disease should be considered in the differential diagnosis of hypervascular mediastinal tumors. Tumor vascularity should be assessed prior to surgery, and preoperative embolization should be considered.